2011
DOI: 10.1159/000330069
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Cadmium Chloride and Methallothionein-1-Bound Cadmium Display Different Accumulation Kinetics and Induce Different Genes in Cells of the Human Nephron

Abstract: Background/Aims: The present study was conducted to investigate the renal tubular handling of inorganic cadmium (Cd2+) by exposing primary human tubular cell cultures to physiologically relevant doses of cadmium chloride (CdCl2). Furthermore, the cellular accumulation of Cd2+ was compared to that of metallothionein-1-bound Cd (Cd7MT-1). Finally, this study aimed to investigate the effect of the accumulation of Cd (both Cd2+ and Cd7MT-1) in renal cells on the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Studies examining responses of healthy primary human kidney epithelial cells to Cd exposure and other nephrotoxicants demonstrate findings similar to our results with the RPTEC/TERT1 cell line [45, 46]. In healthy primary human kidney cells, Cucu et al (2011) found that exposure to concentrations as low as 0.5 µM Cd significantly increased MTIA gene expression after 3 hours followed by a subsequent decline after 24 hours.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies examining responses of healthy primary human kidney epithelial cells to Cd exposure and other nephrotoxicants demonstrate findings similar to our results with the RPTEC/TERT1 cell line [45, 46]. In healthy primary human kidney cells, Cucu et al (2011) found that exposure to concentrations as low as 0.5 µM Cd significantly increased MTIA gene expression after 3 hours followed by a subsequent decline after 24 hours.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy primary human kidney cells, Cucu et al (2011) found that exposure to concentrations as low as 0.5 µM Cd significantly increased MTIA gene expression after 3 hours followed by a subsequent decline after 24 hours. Additionally, significant increases in HMOX1 gene expression were demonstrated after exposure to 0.5 µM Cd indicating an oxidative stress response [45]. A study by Li et al (2013) compared healthy primary human kidney cells to two commonly used virally immortalized kidney cell lines, Human Kidney 2 (HK-2) and Lewis Lung Cancer-Porcine Kidney 1 (LLC-PK1).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 activity can also increase as a result of oxidant stress (Cucu et al, 2011). This is consistent with the present data indicating an oxidant stress response occurred with cadmium in CCT-LC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings demonstrate that HO-1 and HIF-1A are both activated when the CCT-LC cells have acquired multiple tumor cell characteristics, potentially indicating adaptive responses to oxidative conditions. HO-1 is considered an antioxidative protein and is inducible by cadmium exposure (Cucu et al, 2011). HIF-1 can be induced by cadmium through production of reactive oxygen species (Jing et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Amara et al (2011) and Singh et al (2007) mentioned that the damaged central nervous system and DNA or cancer progression appeared as consequences of Cd exposure. Cadmium also causes severe soft tissues and bone damages (Cucu et al, 2011;Ercal et al, 2001;Ersan et al, 2008). Cadmium is known to enhance the production of reactive oxygen species (ROS) (Liu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%